Differentiating between fresh and frozen-thawed fish fillets by mitochondrial permeability measurement. (November 2022) - Bouchendhomme, Tiffanie; Soret, Méline; Devin, Anne; Pasdois, Philippe; Grard, Thierry; Lencel, Philippe
Abstract: In this study, we investigated the properties of mitochondria to discriminate fresh from frozen-thawed fish fillets. Mitochondria were isolated from gilthead seabream fillets and the impact of freezing was evaluated by measuring the permeability of mitochondrial membranes. Freezing led to permeabilization of mitochondrial inner membranes to reduced nicotinamide adenine dinucleotide (NADH). The increase in permeability related to freezing shock was compared to the physiological permeabilization of mitochondria isolated from gilthead seabream fillets stored at 4 °C. Two approaches were chosen to measure the increase in permeability: a spectrophotometric method to measure the consumption of NADH by complex I, and an oxygraphic method to measure O2 consumption by respiratory chains after exposure of mitochondria to NADH. Mitochondria isolated from frozen-thawed fillets were highly permeable to NADH and were no longer sensitive to a membrane permeabilizing agent: alamethicin. Altogether, our scientific approach allowed us to discriminate mitochondria isolated from fillets that have been exposed or not to a freezing shock (−80 °C) and thus to discriminate between fresh and frozen-thawed fish fillets. Highlights: It is difficult to differentiate between fresh and frozen-thawed fish fillets. Mitochondria were extracted from fish fillets and effects of freezing were assessed. Freezing caused permeabilization of mitochondria to NADH. Two methods were used to assess permeability: spectrophotometry and oxygraphy. Both techniques identified mitochondria isolated from fish exposed to freezing shock.